Haemophilia and the kidney: assessment after 11-year follow-up. Issue 6355 (4th December 1982) - Small, S; Rose, P E; McMillan, N; Belch, J J; Rolfe, E B; Forbes, C D; Stuart, J
Abstract : Radiological and biochemical investigations of renal function were performed in 57 patients with haemophilia, 27 of whom had been previously investigated in 1969. Although one-third of patients had a renal radiographic abnormality, only two had abnormalities persisting since 1969 and attributable to renal bleeding. Isotope renography was a sensitive indicator of renal abnormality whereas a history of haematuria was a poor discriminator for patients with abnormal intravenous urograms or impaired creatinine clearance. Haematuria was not associated with progressive loss of renal function and its natural history in haemophilia is probably benign.